A study on the relationship of two admissions tests and the academic performance of DLSC college freshmen, 1967-1968 - Cruz, Maria Leonor B. (Animo Repository, 1969)
v. 1.This study investigates the relationship between two standardized ability tests and the academic performance of college freshmen as measured by their grades. The subjects of the study were the 1967-1968 De La Salle College freshmen. Coefficients of correlation were computed for the two standardized tests, for each test and their relationship with the First Semester academic performance, and for each test part and corresponding subject marks. Results showed, that in all cases, the SCAT (School and College Ability Test) was a better predictor of academic performance than the ACE (American Council on Education Psychological Examination for College Freshmen). Regression equations to determine the cut-off scores were also computed. It was concluded that the SCAT should replace the ACE test, in order to provide the admissions officers with a better predicting instrument in screening applicants. Also, the recommended cut-off scores for the test were given. It was further recommended that validation studies be continued due to the changes in ability levels, intelligence, and test-orientation of the school population. v. 2. This paper is an exploratory study which attempts to establish tentative norms for the students of De La Salle College and to compare the mean traits of the U.S. college students to the traits of Filipino college students at De La Salle. The samples for this study were 130 self-referred De La Salle College students, from the first year to the terminal year, with an average age of 20 years. The means and standard deviations for each of the sixteen factors were computed. Based on these computations, the tentative De La Salle College norms table was formulated and compared with the U.S. college students' norms. Based on the raw scores, a comparison of the average mean traits of each group indicated that: 1.) The De la Salle College students appeared to be more intelligent (Factor B) than the U.S. College students, with the De La Salle mean at 8.9 and the U.S. mean at 7.7. 2.) The U.S. College students' mean score for Factor C indicated that they were more emotionally stable and that the De La Salle students tended to be affected by feelings. 3.) The De La Salle students tended to be more trusting (Factor L), with a mean of 10.7, than their American counterpart. 4.) On Factor F, the U.S. College students were shown to be more happy-go-lucky and the De La Salle students reflected a more serious trait. 5.) The U.S. College students tended to be more venturesome, as reflected by their mean score for Factor H, while the Filipino students were more shy and restrained. The De La Salle mean scores for the rest of the other 16 factors, were more or less equivalent to the average mean scores of the U.S. College students. Based on the results of this study, it was recommended that further researches based on larger samples be conducted on this test. Furthermore, the use of the test was recommended to be continued since the findings of this initial study was found to be valid for the De la Salle students.